2020
DOI: 10.1016/j.jenvman.2020.110783
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical oxidation of butyl paraben on boron doped diamond in environmental matrices and comparison with sulfate radical-AOP

Abstract: The electrochemical oxidation (EO) of butyl paraben (BP) over boron-doped diamond (BDD) anode was studied in this work. Emphasis was put on degradation performance in various actual water matrices, including secondary treated wastewater (WW), bottled water (BW), surface water (SW), ultrapure water (UW), and ultrapure water spiked with humic acid (HA). Experiments were performed utilizing 0.1 M Na 2 SO 4 as the electrolyte. Interestingly, matrix complexity was found to favor BP degradation, i.e. in the order WW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 57 publications
3
12
0
Order By: Relevance
“…Nevertheless, to ensure the pH modification is not responsible for this amelioration, an AO test was done at pH 3, where slight differences were detected (Table 5). Similar results about the minor effect of initial pH on the oxidation of organic pollutants using BDD oxidation have been previously reported [44,45]. Moreover, an initial EF test at neutral pH was carried out, improving slightly the mineralization performance when compared to AO.…”
Section: Ef Treatmentsupporting
confidence: 85%
“…Nevertheless, to ensure the pH modification is not responsible for this amelioration, an AO test was done at pH 3, where slight differences were detected (Table 5). Similar results about the minor effect of initial pH on the oxidation of organic pollutants using BDD oxidation have been previously reported [44,45]. Moreover, an initial EF test at neutral pH was carried out, improving slightly the mineralization performance when compared to AO.…”
Section: Ef Treatmentsupporting
confidence: 85%
“…reported that the rate of BDD oxidation of parabens decreased at greater concentrations. In other studies, Pueyo et al 27 . studied the influence of butyl paraben concentration on its degradation at 50 mA cm −2 , and showed that complete degradation could be reached after 15 min of reaction in the range 0.25–1 mg L −1 with the rate constant decreasing from 0.35 to 0.12 min −1 , respectively.…”
Section: Resultsmentioning
confidence: 95%
“…Although the respective individual interactions cannot easily be identified and quantified, it seems that the role of chloride is critical, increasing the reaction rate by an order of magnitude in those experiments where UPW had 50–250 mg L −1 chloride added. This may be ascribed to the formation of active chlorine species according to Eqns (1)–(4) that complement hydroxyl radicals in the degradation of DEX: 24 2ClCl2+2e0.25em ClCl˙+2e0.25em Cl+OHHOCl+e0.25em HOClClO+H+0.25em The beneficial role of Cl − in the kinetics of electrochemical oxidation of organics has been demonstrated before 23,24,27 . However, it should be noted that the presence of chloride may cause the production of organochlorinated by‐products, which may be implicated in increased ecotoxicity 28,29 .…”
Section: Resultsmentioning
confidence: 99%
“…In this condition, 95% of BuP was degraded in 180 min in the presence of 0.1 M of K 4 P 2 O 7 as electrolyte and 40 µM of CTAC on glassy carbon. The study by Pueyo et al [114] proved the good performance of BDD over platinum and stainless-steel anodes. This should be expected, since one of the good characteristics of BDD is its good working performance, but the disadvantages such as its high cost can make it difficult to implement electrochemical experiments with this anode.…”
Section: Electrochemical Technologiesmentioning
confidence: 98%
“…The removal of BuP by electrochemical technologies was also investigated. Pueyo et al [114] used electrochemical oxidation, using different materials as anode and stainless-steel as cathode, to remove 0.5 mg/L of BuP in an electrolyte solution of 0.1 M of Na 2 SO 4 . BDD anode allowed a BuP removal of 100% in 15 min, while stainless steel and platinum only achieved 40% and 18% degradation, respectively.…”
Section: Electrochemical Technologiesmentioning
confidence: 99%